2018
DOI: 10.1002/eco.1953
|View full text |Cite
|
Sign up to set email alerts
|

A physical framework for evaluating net effects of wet meadow restoration on late‐summer streamflow

Abstract: Restoration of degraded wet meadows found on upland valley floors has been proposed to achieve a range of ecological benefits, including augmenting late‐season streamflow. There are, however, few field and modelling studies documenting hydrologic changes following restoration that can be used to validate this expectation, and published changes in groundwater levels and streamflow following restoration are inconclusive. Here, we assess the streamflow benefit that can be obtained by wet‐meadow restoration using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 54 publications
1
16
1
Order By: Relevance
“…Mass balance discrepancies are common in the literature on meadow restoration and its contributions to baseflow (e.g., Tague et al , corrected in Aylward and Merrill ; Wegener et al ), often due to the magnitude and complexity of incoming hydrologic fluxes. Generally, previous research suggests that meadows have neither the storage capacity nor the drainage dynamics to impact late summer baseflow in climates with arid summers (Hammersmark et al ; Essaid and Hill ; Nash et al ). The mass balance approach we present here should be useful for checking estimates of streamflow‐related outcomes in future meadow restoration projects.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Mass balance discrepancies are common in the literature on meadow restoration and its contributions to baseflow (e.g., Tague et al , corrected in Aylward and Merrill ; Wegener et al ), often due to the magnitude and complexity of incoming hydrologic fluxes. Generally, previous research suggests that meadows have neither the storage capacity nor the drainage dynamics to impact late summer baseflow in climates with arid summers (Hammersmark et al ; Essaid and Hill ; Nash et al ). The mass balance approach we present here should be useful for checking estimates of streamflow‐related outcomes in future meadow restoration projects.…”
Section: Resultsmentioning
confidence: 98%
“…The potential of wet meadow restoration to augment summer streamflow has motivated considerable interest from states in the Western United States seeking to mitigate against increasingly variable summer water availability. Several modelling studies have suggested that meadow restoration should decrease summer streamflow, due in part to more evapotranspirative use and reduced hydraulic gradients (e.g., Hammersmark et al ; Essaid and Hill ; Nash et al ). Field data has, however, been relatively scarce given how difficult it can be to accurately constrain the dynamic and often small hydrologic fluxes in these environments.…”
Section: Introductionmentioning
confidence: 99%
“…Channel incision has the added effect of sometimes lowering water tables under adjacent floodplains (Bilyeu, Cooper, & Hobbs, ; Nash, Selker, Grant, Lewis, & Noël, ). Unless these water tables are supplemented from other sources, such as subsurface flow or shallow groundwater from adjacent hillslopes, decreased availability of subsurface moisture for floodplain vegetation is likely to occur during late summer.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, an early assessment of floodplain systems in the eastern United States found bankfull recurrence intervals of 1.1-3 years (Leopold, Wolman, & Miller, 1964). A more recent study of 76 streams across Oregon and Washington (Castro & Jackson, 2001) found bankfull flows had an average recurrence interval of Channel incision has the added effect of sometimes lowering water tables under adjacent floodplains (Bilyeu, Cooper, & Hobbs, 2008;Nash, Selker, Grant, Lewis, & Noël, 2018). Unless these water tables are supplemented from other sources, such as subsurface flow or shallow groundwater from adjacent hillslopes, decreased availability of subsurface moisture for floodplain vegetation is likely to occur during late summer.…”
Section: Discussionmentioning
confidence: 99%
“…Though the implementation of these methods has a strong theoretical and technical foundation, skepticism lingers—particularly about the efficacy of hand‐built, beaver‐inspired structures, and beaver coexistence. In particular, recent publications have called into question the practicality of achieving watershed‐scale changes through beaver landscape modifications or anthropogenic beaver mimicry (Nash et al, 2018; Nash et al, 2021; Pilliod et al, 2017). This is despite countless of years of Indigenous knowledge on sustainable riparian and beaver management (Albert & Trimble, 2000; Blackfeet Nation, 2018; Blackfeet Nation & Levitus, 2019; Feit, 1986; Gadgil et al, 1993; Keeble‐Toll, 2018; Kimmerer, 2000; Kimmerer & Lake, 2001; Sherriff, 2021) and over a century of published data, experiments and analyses (Ives, 1942; Morgan, 1868; Neff, 1957; Ruedemann & Schoonmaker, 1938; Seton, 1929) documenting enhanced hyporheic engagement (Briggs et al, 2013; Janzen & Westbrook, 2011; X. Wang et al, 2018), improved water quality (Cornell et al, 2011; Lazar et al, 2015; Puttock et al, 2017, 2018; Shepherd & Nairn, 2020, 2021), naturalized flow timing (Burchsted et al, 2010), failure of traditional engineering approaches to restoration (D. M. Thompson & Stull, 2002), and wildfire resilience (Fairfax & Whittle, 2020; Foster et al, 2020; Weirich, 2021; Whipple, 2019).…”
Section: Introduction: Beavers the Climate Action Planmentioning
confidence: 99%